Produção leiteira e desenvolvimento regional: uma análise dos agentes da cadeia produtiva na região noroeste do estado do Rio Grande do Sul - Moraes, Alexandra de (2010)
Milk, a food source for humans and with economic importance, is an alternative production, income generation and employment with influence in local and regional development. The Northwestern Rio Grande do Sul is characterized by the family farm and between the small farms activities the milk production is a source of income, employment and opportunity promoting the development of agribusiness. This study aims to contextualize the production chain of milk presenting relevant aspects that influence their performance through a characterization from the agents which compose it. Based on the data collected, we present the analysis on the linkages between those involved in the milk chain and how these contribute to the management and promotion of regional development. The work was based on a qualitative study from primary and secondary data. The primary data were collected through semi-structured interviews with integrants of the institutions of the milk chain in the northwestern Rio Grande do Sul. Secondary data were collected in books, research articles, newspapers, internet and events. The study was based on theoretical models by Ferraz, Kupfer and Haguenauer (1995) for describing the competitive framework of companies and by Jank and Galan (1998) for contextualizing and analyzing the structure and integration of players that compose the milk production chain in the region mentioned above. According to information from the Bulletin for Milk (2009), the referred region is holding the highest milk production in RS gathering, nowadays, the structure and investments which is the highest source of income and employment. The results indicate that the dairy production chain in the northwestern Rio Grande do Sul is processed by the integration of different actors which compose itself. The chain is also concerned about the competitiveness of its various segments, the environment and proposes improvements in quality of life in dairy agribusiness activity, making it a self-sustainable alternative in terms of local and regional development.